EFL Preservice Teachers’ Perception on Communicative Language Teaching Integrated with Digital Literacy in Improving Teaching Skills - Haerazi Haerazi; Lalu Ari Irawan (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
This study explores EFL preservice teachers’ perceptions of Communicative Language Teaching (CLT) integrated with digital literacy in improving teaching skills. In contemporary EFL contexts, teachers are expected to facilitate meaningful communication while also using digital tools to support interactive, flexible, and student-centered learning. Although CLT and digital literacy have been widely discussed separately, limited attention has been given to how their integration is perceived by preservice teachers as future English educators. This study employed a qualitative research design involving 85 EFL preservice teachers enrolled in English Language Education programs at universities in West Nusa Tenggara, Indonesia. Data were collected through interviews and analyzed using qualitative procedures of data condensation, data display, and conclusion drawing. The findings revealed that participants perceived CLT integrated with digital literacy positively because it promoted authentic communication, increased student engagement, and supported interactive learning. Digital tools were viewed as useful for extending communicative activities through online discussions, collaborative writing, video presentations, and digital learning platforms. The participants also believed that this integration improved their teaching skills, particularly in lesson planning, digital tool selection, classroom interaction management, creative material development, assessment, feedback, and professional confidence. However, they emphasized that successful implementation requires adequate training, stable internet access, digital facilities, and opportunities for practice. The study concludes that integrating CLT with digital literacy can strengthen preservice teachers’ pedagogical, technological, and communicative competence. It suggests that EFL teacher education programs should provide practice-based training that connects communicative pedagogy with digital literacy development for sustainable future classroom teaching practice effectively.